Intense femtosecond optical pulse shaping approaches to spatiotemporal control - Goswami, Debabrata (Frontiers in Chemistry, 2023)
For studying any event, measurement can never be enough; “control” is required. This means mere passive tracking of the event is insufficient and being able to manipulate it is necessary. To maximize this capability to exert control and manipulate, both spatial and temporal domains need to be jointly accounted for, which has remained an intractable problem at microscopic scales. Simultaneous control of dynamics and position of an observable event requires a holistic combination of spatial and temporal control principles, which gives rise to the field of spatiotemporal control. For this, we present a novel femtosecond pulse-shaping approach. We explain how to achieve spatiotemporal control by spatially manipulating the system through trapping and subsequently or simultaneously exerting temporal control using shaped femtosecond pulses. By leveraging ultrafast femtosecond lasers, the prospect of having temporal control of molecular dynamics increases, and it becomes possible to circumvent the relaxation processes at microscopic timescales. Optical trapping is an exemplary demonstration of spatial control that results in the immobilization of microscopic objects with radiation pressure from a tightly focused laser beam. Conventional single-beam optical tweezers use continuous-wave (CW) lasers for achieving spatial control through photon fluxes, but these lack temporal control knobs. We use a femtosecond high repetition rate (HRR) pulsed laser to bypass this lack of dynamical control in the time domain for optical trapping studies. From a technological viewpoint, the high photon flux requirement of stable optical tweezers necessitates femtosecond pulse shaping at HRR, which has been a barrier until the recent Megahertz pulse shaping developments. Finally, recognizing the theoretical distinction between tweezers with femtosecond pulses and CW lasers is of paramount interest. Nonlinear optical (NLO) interactions must be included prima-facie to understand pulsed laser tweezers in areas where they excel, like the two-photon-fluorescence-based detection. We show that our theoretical model can holistically address the common drawback of all tweezers. We are able to mitigate the effects of laser-induced heating by balancing this with femtosecond laser-induced NLO effects. An interesting side-product of HRR femtosecond-laser-induced thermal lens is the development of femtosecond thermal lens spectroscopy (FTLS) and its ability to provide sensitive molecular detection.